Audit of Electroconvulsive Therapy (ECT) Service Provision: Current Practices and Adherence to Guidelines at Punjab Institute of Mental Health, Lahore, Pakistan - Muhammad Sheikh; Ahmad Irfan; Adnan Sarwar; Muhammad Ahmed; Haris Ali (BJPsych Open)
Aims: Our audit aimed to assess the quality of care received by patients undergoing Electroconvulsive Therapy (ECT) treatment in one of the largest psychiatric hospitals in Pakistan. The current practices regarding the consent process, recording of vitals during ECT, and monitoring of clinical response and cognitive side effects were assessed. Adherence to guidelines set forth by the Royal College of Psychiatrists was examined.